The Effectiveness Analysis of Dompet Dhuafa Ekselensia Tahfizh School: Evaluating Educational and Management Performance - Fitria, Lia; Priantina, Anita; Haryadi, Pedri (Universitas Airlangga, 2025)
Ekselensia Tahfizh School (e-Tahfizh) is a human resource development program with a focus on memorizing Al-Qur'an, dirasah Islamiyah, and leadership under the auspices of the Lembaga Amil Zakat (LAZ) Dompet Dhuafa. This study aims to determine the extent to which the effectiveness of the e-Tahfizh program in helping beneficiaries feel a change in welfare in their lives. This study uses a quantitative and descriptive qualitative approach with a random sample technique and data collection through interviews and questionnaires to 28 alumni, as well as applying the CIBEST model and T-test to measure changes in spiritual well-being before and after undergoing program coaching. The results showed that the program was effective, where the spiritual well-being index increased from 75% to 82.14% before and after becoming an alumnus of the e-Tahfizh program. In addition, the t-test also showed statistical significance with a p-value of 0.022 (one-way) and 0.044 (two-way), so the statistical test results were declared significant because they were smaller than 0.05. The practical implications of this research show that ZISWAF-based education could improve the spiritual welfare of underprivileged communities. The e-Tahfizh model could expand access to Islamic education and optimize the role of ZISWAF in human resource development. Dompet Dhuafa continues to encourage evaluation to improve program quality and expand access to Islamic values-based education.